The transformation of religious communication Knowledge among Buddhist religious instructors: A case study on the implementation of Buddhist communication science - Adi Gautama, Sidartha (Universitas Ahmad Dahlan, 2025)
This study investigates the transformation of religious communication among Buddhist instructors in Bandar Lampung, Indonesia, focusing on how their pedagogical practices have adapted to socio-cultural changes and digital technology. Using a qualitative single case study approach, data were collected through in-depth interviews, participant observation, and documentation involving ten active instructors across various viharas. Findings show a clear shift from monologic, doctrinal transmission to dialogic, participatory, and digitally mediated communication practices. Instructors increasingly employ platforms such as WhatsApp, Zoom, and Facebook Live to engage broader audiences while upholding Buddhist ethical principles such as samma vaca (right speech), mettā (loving-kindness), and karuṇa (compassion). The study highlights a strong need for structured training and formal certification, particularly among instructors with non-religious academic backgrounds. Competencies in public speaking, digital media, and interpersonal communication are identified as critical to effective outreach. Motivation among instructors is closely linked to institutional recognition and support. This study is limited in scope, focusing solely on a single city and religious group, and access to private digital outreach sessions was restricted. Future research should incorporate cross-regional and cross-religious comparisons to explore how religious communication evolves across digital cultures in Southeast Asia. This research contributes to the development of religious communication as a subfield within communication studies and calls for integrating ethical, spiritual, and technological dimensions in the training of religious communicators.